Interactive Multimedia Educational Games on Water Cycle Material Based on Local Wisdom to Improve Science Learning Outcomes in Grade V Elementary School - I Wayan Artayana; Ni Ketut Suarni; Kadek Yudiana (Mimbar Pendidikan Indonesia, 2025)
21st century education emphasizes learning that utilizes technology to improve the quality of the learning process. The integration of technology allows teachers to design innovative learning media, including those that highlight local wisdom. However, in practice, local wisdom is still rarely used as a source and medium of learning in elementary schools. This study aims to develop and test the effectiveness of interactive multimedia educational games based on local wisdom in improving science learning outcomes for fifth-grade students. The study uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade students, with data collected through observation and tests. The instruments used included a rating scale to assess feasibility and practicality, as well as multiple-choice tests to measure learning outcomes. Data analysis was conducted using average scores to assess validity and practicality, as well as a correlated t-test to measure the effectiveness of the media. The research results showed an average media feasibility score of 4.83, a media test score of 4.42, and a design feasibility score of 4.60, all of which were very high. The practicality test by teachers and students obtained 4.92 and 4.94, respectively, with a very good category. The t-test produced a significance value of 0.000 (<0.05), indicating that this interactive multimedia is effective in improving learning outcomes. These findings have implications for the development of technology-based learning media and local wisdom to support 21st-century learning quality.